Membangun Resiliensi Mental Mahasiswa di Era Digital: Integrasi Pendekatan Psikologi dan Nilai Spiritual di Lingkungan Kampus - Mubarok, Muhammad Afin (Maliki Interdisciplinary Journal, 2026)
Gen Z students in the digital era face significant mental health vulnerabilities due to academic pressures and complex social dynamics. This article aims to formulate strategies for strengthening student resilience by integrating clinical psychology approaches with spiritual values. Synthesizing literature from research conducted by lecturers at UIN Maulana Malik Ibrahim Malang, this study combines data on student mental health profiles in Islamic higher education with Cognitive Behavior Modification (CBM) techniques and the model of Islamic science integration. The discussion demonstrates that effective stress management requires two primary foundations: the cognitive ability to restructure negative thought patterns and spiritual fortitude to interpret academic challenges as a form of worship (ibadah) and self-maturation. These findings underscore that campus-based mental health interventions cannot be solely clinical but must be holistic. The synergy between psychological skills and transcendental values proves effective in fostering adaptive and resilient student character. Consequently, this article recommends strengthening counseling services based on the integration of science and religion as both preventive and curative solutions within the campus environment.